Perencanaan Strategi Manajemen pada Kasus Perusahaan Distributor Spare Part Motor - Johanes Fernandes Andry; Liem Bambang Sugiyanto (Universitas Bunda Mulia, 2023)
Several Motor Spare Part Distributor Companies have problems in planning management strategies to increase marketing. Therefore the authors conducted this research so that the company has a strategic management plan by utilizing technology, namely by implementing an information system, especially in the field of marketing, therefore a management strategy is needed to align information technology strategy with the company's business activities and strategy by adjusting the company's internal conditions. Researchers carry out various activities in research, namely literature review, collecting data from companies, Internal and external business analysis and making enterprise architecture blueprints and information technology portfolios that will be used. The research results show that the company has adequate information system planning for current and future business processes by mapping them into the application portfolio. The company's e-commerce website shows very strategic results in increasing the marketing of the distributor company.